Pengaruh Internal Information Quality, Foreign Institutional Ownership dan Financial Constraints terhadap Cash Holding Pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Ammanda, Afifah; Hamidi, Masyhuri; Adrianto, Fajri (SAFE-Network, 2024)
This study aims to look at the factors that influence cash holding in non-financial companies. The independent variables use in this study are internal information quality, foreign institutional ownership and financial constraints and this study uses control variables firm size, leverage and growth opportunity. The data analysis technique used in this research is panel data regression. Based on the results of the research conducted, it was found that the internal information quality has a negative and significant effect on cash holding. Foreign institutional ownership has no significant effect on cash holding. Financial constraints also has no significant effect on cash holding. The control variable firm size has no significant effect on cash holding. The control variable leverage has a negative and significant effect on cash holding. The control variable growth opportunity also has a negative and significant effect on cash holding.